2017
DOI: 10.3390/jcm6100091
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Minimal Residual Disease Detection by Multiparameter Flow Cytometry, ASO-qPCR, Droplet Digital PCR, and Deep Sequencing in Patients with Multiple Myeloma Who Underwent Autologous Stem Cell Transplantation

Abstract: Multiple myeloma (MM) is a hematological malignancy with a poor prognosis, characterized by clonal proliferation of plasma cells in the bone marrow (BM). Relapse due to undetected minimal residual disease (MRD) is the leading cause of death among patients with MM. This review summarizes the methods and prognostic value of MRD assessment in BM and autografts from MM patients who underwent autologous stem cell transplantation (ASCT) by multiparameter flow cytometry (MFC), allele-specific oligonucleotide real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…ASO‐qPCR is a powerful method for MRD evaluation with sensitivity comparable to other methods . The sensitivity of our assay reached 10 −4 ‐10 −6 and corresponds to sensitivities described by other studies . However, applicability of ASO‐qPCR is often limited by technical complexity and variety of technical problems .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…ASO‐qPCR is a powerful method for MRD evaluation with sensitivity comparable to other methods . The sensitivity of our assay reached 10 −4 ‐10 −6 and corresponds to sensitivities described by other studies . However, applicability of ASO‐qPCR is often limited by technical complexity and variety of technical problems .…”
Section: Discussionsupporting
confidence: 74%
“…35,36 The sensitivity of our assay reached 10 −4 -10 −6 and corresponds to sensitivities described by other studies. 30,37 However, applicability of ASO-qPCR is often limited by technical complexity and variety of technical problems. 38 In our study, lower applicability mirrors in the number of analyzed vs. enrolled patients (45/112) with main reason for exclusion being the inability to identify patient-specific VDJ rearrangement (see Appendix S1 for details).…”
Section: Discussionmentioning
confidence: 99%
“…Our model could be extended and refined by considering the interaction between lesions in the growth process, such as done in (Baratchart et al, 2015;Benzekry et al, 2017) One could in particular investigate related models for other observed parameters for MM, such as laboratory parameters that are known to correlate with the progression of the disease (Mai et al, 2015;Wennmann et al, 2018), genetic markers or cell-surface proteins measured with flow-cytometry (Flores-Montero et al, 2017). Next-generation sequencing, which is becoming available and permits to distinguish different clonal phenotypes of plasma cells (Takamatsu, 2017) Hartung, N., Mollard, E., Barbolosi, D., Benabdallah, A., Chapuisat, G., Henry, G., Giacometti, S., Iliadis, A., Ciccolini, J., Faivre, C., Hubert, F., 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Standardized in different consortia [37] Limited standardization [37] Limited standardization [37] Limited Standardization [32] Limited Standardization [37]…”
Section: Standardizationmentioning
confidence: 99%
“…No [37] No [37] Yes [37] Yes [32] No [37] 3.1. Multiparametric Flow Cytometry MRD detection by phenotype identifies surface antigen markers and can differentiate normal bone marrow lymphocytes and myeloid cells from mutated leukemic progenitor cells.…”
Section: Use Of Patient-specific Reagentmentioning
confidence: 99%